Male mating success and female choice in the lekking black grouse - Rintamäki, Pekka (1995)
Behaviour of lekking black grouse males and females were studied during years 1987-1994 in Central Finland. Most of the observed birds had been measured and colour-ringed. Females prefer central, clustered males. However, females do not favour specific sites within the central area of the lek. Over the seasons successful males did not change their territory position but unsuccessful males tried to gain some benefit by gathering around these attractive males. Males gather to lek and defend their territories also in autumn. This lekking activity is likely to be adaptive behaviour for ensuring possibilities to achieve copulations in the spring. Less successful males at the edge of the lek were most asymmetrical in tarsus length suggesting poor condition among these males. Male behavioural traits did not predict particularly well male mating success, even if lek attendance and lyre posture had significant effects. Among the morphological traits, size had some impact so that larger males were more successful. Black grouse females did not sample males randomly, since they targeted their visits to central males. Females are free to sample several males simultaneously which suggests the pool comparison tactic. Heavy females visited more males than lighter females suggesting that sampling includes some costs even in this lekking species.